Maternally-Derived Antibody and Seroconversion to Infectious Bronchitis Virus in Chicken - Paul, Narayan Chandra; Khan, M Shahidur Rahman; Islam, Shaiful; Akhter, AHM Taslima; Shil, Niraj Kanti (Bangladesh Journal of Microbiology, 2010)
An investigation was conducted with a view to determining the persistence of maternally-derived antibody (MDA) against infectious bronchitis virus (IBV) in chicks as well as seroconversion of IBV in relation to age and gender of chicks in field condition. Determination of antibody titre was performed by indirect enzymelinked immunosorbent assay (iELISA). The existence of MDA was calculated in Group A (n = 20) and Group B (n = 15) originating from parents vaccinated against IBV and with no such history respectively. In case of group A, titres of serum samples obtained were 5361.23 ± 854.09, 2567.58 ± 763.61, 808 ± 751.361, 432.29 ± 47.11, 178.36 ± 88.28, 184.58 ± 93.6, 80.89 ± 70.11 and 43.55 ± 32.92 on day 1, 5, 9, 13, 17, 21, 25 and 29 days aged birds respectively. On the other hand, sera samples of group B manifested a titre of 3285.18 ± 685.03, 2219.16 ± 419.77, 1783.62 ± 219.84, 589.01 ± 249.63, 186.66 ± 88.21, 178.36 ± 202.02, 105.77 ± 75.69 and 41.34 ± 69.28 on same schedule. It was further revealed that chicks with ancestor of non-vaccinated parents showed higher MDA titre up to 9th day of age. This might have happened due to exposure of field virus to the parent birds. As regards seroconversion, it was observed that 100, 20 and 80% of serum samples collected from chickens of 0-2 weeks, 3-4 weeks and 4 months of age were positive to IBV specific antibody respectively, whereas no serum sample was positive in case of 5-7 weeks aged birds. When considered the gender of birds, it was revealed that sera from the female showed 58.33% seropositivity against 25% from male. Maternally-derived antibody (MDA) might protect the chickens up to 9 days of age and since MDA could interfere vaccination, it should not be performed before such age. Keywords: Maternally-derived antibody (MDA); Infectious bronchitis virus (IBV); antibody titre; Seroconversion; Chicks DOI: http://dx.doi.org/10.3329/bjm.v25i1.4857 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 53-56